2021
DOI: 10.1111/1755-0998.13369
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome level reference of Atlantic halibut Hippoglossushippoglossus provides insight into the evolution of sexual determination systems

Abstract: Changes in the genetic mechanisms that control sexual determination have occurred independently across the tree of life, and with exceptional frequency in teleost fishes.To investigate the genomic changes underlying the evolution of sexual determination, we sequenced a chromosome-level genome, multitissue transcriptomes, and reduced representation population data for the Atlantic halibut (Hippoglossus hippoglossus), which has an XY/XX sex determination mechanism and has recently diverged (0.9-3.8 Ma) from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 55 publications
6
29
0
Order By: Relevance
“…We generated a final genome assembly of 598.5 Mb, with overall high contiguity (N50=25MB, N90=20MB), of which 96.35% was comprised into 24 chromosome-length scaffolds (GenBank accession: GCA_006182925.3). These 24 scaffolds are consistent with the number of diploid chromosomes (2n=48) for Atlantic Halibut (Einfeldt et al 2021) and Pacific Halibut (GCA_013339905.1). The Hi-C data supported a high degree of accuracy in the overall assembly into these 24 scaffolds, as indicated by the strong concentration of data points along the diagonal rather than elsewhere in the contact maps (Figure S1).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…We generated a final genome assembly of 598.5 Mb, with overall high contiguity (N50=25MB, N90=20MB), of which 96.35% was comprised into 24 chromosome-length scaffolds (GenBank accession: GCA_006182925.3). These 24 scaffolds are consistent with the number of diploid chromosomes (2n=48) for Atlantic Halibut (Einfeldt et al 2021) and Pacific Halibut (GCA_013339905.1). The Hi-C data supported a high degree of accuracy in the overall assembly into these 24 scaffolds, as indicated by the strong concentration of data points along the diagonal rather than elsewhere in the contact maps (Figure S1).…”
Section: Resultssupporting
confidence: 78%
“…Chr10 and Chr21 neither correspond to locations where sexdetermining regions have been defined in other species (Figure 1, Table1). Overall, the resolved sex-determining system in Greenland Halibut is highly consistent with the rapid turnover of sex chromosomes in fish, particularly in flatfish, given that the Atlantic Halibut has also undergone a recent evolution of an XY sex-determination mechanism (Einfeldt et al 2021).…”
Section:  Nascent Xy Sex Determination Systemsupporting
confidence: 56%
See 2 more Smart Citations
“…(2017) found that the major chr7 XY locus previously identified in Malawi Mbuna cichlids determined sex in a population of A. calliptera from Lake Malawi. Despite only mapping the effect to megabase-scale resolution, they postulated that a variant in the gonadal soma-derived factor ( gsdf ) gene on chromosome 7 was responsible for dictating sex given its repeated role in sex determination in other fish species (Einfeldt et al ., 2021; Jiang et al ., 2016; Kaneko et al ., 2015; Myosho et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%